Rancang Bangun Alat Penyiraman Tanaman Tomat Otomatis Menggunakan Sensor Rtc Berbasis Arduino Uno - Kevin Alfanugraha (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Water is an important thing that is needed by tomato plants because water is the main component in compiling plant tissue cells. Therefore, the purpose of this research is to design an automatic tomato plant watering tool using an Arduino Uno-based RTC sensor which is expected to be able to water the plants automatically with a set time. To achieve this goal, Arduino IDE software is used to program the tool. The hardware used is electronic components including Arduino Uno board, RTC Sensor, Temperature Sensor, Humidity Sensor, LCD, Relay, ESP 8266, Adapter, DC to DC, Pump, Blynk Apps, and Android Smartphone. Tests conducted on this tool include: Testing the need for good water for tomato plants. Testing soil moisture that is suitable for tomato plants. Testing the air temperature that is good for tomato plants. Testing the automatic watering scheduling time. The test results are as follows: Water for watering is 3.2 - 3.6 mm per day. Soil moisture for tomato plants is between 60% - 80%. The ambient temperature for tomato plants ranges from 24 - 28°C. Watering scheduling time is done 2 times a day.